Getting over the hurdles to save lives: Incorporating perceived barriers into theory of planned behaviour (TPB) model to predict stated intention among Hong Kong trained laymen - Victor C.W. Tam; Nelson C.Y. Yeung; Anthony Wai Leung Kwok (PLoS ONE, 2026)
Background The ‘Intention-focused model’ is advocated for educating bystanders in Basic Life Support (BLS), consisting of cardiopulmonary resuscitation and automated external defibrillation. Although previous International Consensus on Cardiopulmonary Resuscitation statements have summarised barriers at the scene of out-of-hospital cardiac arrest, few studies have investigated how barriers perceived by trained laypeople affect their intention to deliver BLS (BLS intention) and the underlying mechanisms, especially during the COVID-19 pandemic when global fear of infection was persistently heightened. This study examines the relationship between perceived barriers (PB) and the Theory of Planned Behaviour (TPB) constructs, i.e., attitude, subjective norms (SN), perceived behavioural control (PBC) and BLS intention, as well as the role of concern about infection. Methods A cross-sectional online survey of 678 trained adult laypeople was conducted in 2022 using convenience sampling. Structural equation modelling was used to analyze the relationship between PB subscales, BLS intention, attitude, SN and PBC. Multigroup analysis was used to examine the potential moderating effect of concern about infection. Results A split-construct model consisting of two barrier subscales showed better model fit (χ2/df = 3.224, CFI = 0.966, RMSEA = 0.057) than the lumped-construct model (χ2/df = 3.732, CFI = 0.953, RMSEA = 0.064). Performance-related barriers had a strong significant association with PBC (β = −0.74, P < 0.001), while cultural barriers were significantly associated with attitude (β = −0.34, P < 0.001), and SN ( β = −0.16, P < 0.001) were significant, but not for PBC ( β = 0.01, P = 0.905). Attitude, SN, and PBC had significant effects on BLS intention ( β = 0.14–0.56, Ps < 0.001). Multigroup analysis showed that concern about infection significantly moderated the relationship between cultural barriers and attitude (Low concern: β = −0.474, P < 0.001; High concern: β = −0.326, P < 0.001; Δχ 2 (1)=6.319, P = 0.012). Conclusions This study offers empirical evidence for integrating perceived barriers into an intention-focused model to predict laypersons’ willingness to perform resuscitation. Future research should focus on addressing priority concerns and transforming them into heightened willingness through enhancing positive attitudes, SN and PBC.